background image

16.8. FUNCOID BASES

269

d

α

X

]

α

exp

α

;

α

+ exp

α

[

w

d

F

X

up

x

d

α

X

]

α

ε

;

α

+

ε

[ for some

ε >

0 and

thus by properties of generalized filter bases (

n

d

α

X

]

α

ε

;

α

+

ε

[

X

up

x

o

is a filter base) for

some

X

0

up

x

l

α

X

]

α

exp

α

;

α

+ exp

α

[

w

l

α

X

0

]

α

ε

;

α

+

ε

[

what is impossible by the fact that exp

α

goes infinitely small as

α

→ −∞

and the

fact that we can take

X

=

Z

for some

x

.

Now prove the general case:

Proof.

Suppose that

K

up

d

FCD

S

and thus

h

K

i

x

w

D

d

FCD

S

E

x

. We need

to prove that there is some

L

S

such that

K

w

L

.

Take an ultrafilter

x

.

D

d

FCD

S

E

x

=

d

F

L

S

h

L

i

x

=

d

F

L

S,X

up

x

h

L

i

X

.

h

K

i

x

=

d

F

X

up

x

h

K

i

X

.

Then

h

K

i

X

w

d

F

L

S,X

up

x

h

L

i

X

for every

X

up

x

; thus by properties of

generalized filter bases (

n

h

L

i

X

L

S

o

is a filter base);

h

K

i

X

w

d

F

X

up

x

h

L

i

X

for some

L

S

and thus by properties of generalized

filter bases (

n

h

L

i

X

X

up

x

o

is a filter base) for some

X

0

up

x

h

K

i

X

w h

L

i

X

0

w h

L

i

x

.

So

h

K

i

x

w h

L

i

x

because this equality holds for every

X

up

x

. Therefore

K

w

L

.

Example

1417

.

A base of a funcoid which is not a filter base.

Proof.

Consider

f

= id

FCD

. We know that up

f

is not a filter base. But it is

a base of a funcoid.

Exercise

1418

.

Prove that a set

S

is a filter (on some set) iff

X

0

, . . . , X

n

S

: up(

X

0

u · · · u

X

n

)

S

for every natural

n

.

A similar statement does

not

hold for funcoids:

Example

1419

.

For a set

S

of binary relations

X

0

, . . . , X

n

S

: up(

X

0

u

FCD

· · · u

FCD

X

n

)

S

does not imply that there exists funcoid

f

such that

S

= up

f

.

Proof.

Take

S

0

= up 1

FCD

(where 1

FCD

is the identity funcoid on any infinite

set) and

S

1

=

S

F

S

0

n

up

G

G

up

Γ

F

o

(that is

S

1

=

S

F

up

Γ

1

FCD

up

F

).

Both

S

0

and

S

1

are upper sets.

S

0

6

=

S

1

because 1

FCD

S

0

and 1

FCD

/

S

1

.

The formula in the example works for

S

=

S

0

because

X

0

, . . . , X

n

up 1

FCD

.

It also holds for

S

=

S

1

by the following reason:

Suppose

X

0

, . . . , X

n

S

1

. Then

X

i

w

F

i

where

F

i

S

0

. Consequently (take

into account that Γ is a sublattice of

FCD

)

X

0

, . . . , X

n

w

F

0

u

FCD

· · · u

FCD

F

n

and

so

X

0

u

FCD

· · · u

FCD

X

n

=

X

0

u · · · u

X

n

w

F

0

u

FCD

· · · u

FCD

F

n

w

1

FCD

. Thus

X

0

u · · · u

X

n

up

Γ

1

FCD

S

1

; up(

X

0

u · · · u

X

n

)

S

1

as

S

1

is an upper set.

To finish the proof suppose for the contrary that up

f

0

=

S

0

and up

f

1

=

S

1

for some funcoids

f

0

and

f

1

. In this case

f

0

=

d

FCD

S

0

= 1

FCD

=

d

FCD

up

Γ

1

FCD

=

d

FCD

S

1

=

f

1

and thus

S

0

=

S

1

, contradiction.